Skin Displacement as fascia tissue manipulation at the lower back affects instantaneously the flexion-and extension spine, pelvis, and hip range of motion - van Amstel, Robbert N.; Jaspers, Richard T.; Pool-Goudzwaard, Annelies L. (Frontiers in Physiology, 2022)
Low back pain (LBP), associated with spine, pelvis, and hip mobility impairments can be caused by tight muscle contractions, to protect sensitized lumbar fasciae. Fascia tissue manipulations are used to treat lumbar fascia in LBP. The effect of fascia tissue manipulations through lumbodorsal skin displacement (SKD) on mobility is inconclusive likely depending on the location and displacement direction of the manipulation. This study aimed to assess whether lumbodorsal SKD affects the flexion -and extension range of motion (ROM), in healthy subjects. Furthermore, we aimed to test the effect of SKD at different locations and directions. Finally, to assess intertester and intratester reliability of SKD. Effects of SKD were tested in a motion capture, single-blinded, longitudinal, experimental study. Sixty-three subjects were randomly assigned to SKD- or sham group. SKD group was subjected to either mediolateral directed SKD during flexion or extension movement, versus a sham. The thoracic, lumbar, and hip angles and finger floor distance were measured to assess the change in ROM. Statistics indicated that the effect size in instantaneously change of flexion -and extension ROM by SKD was large (Effect size: flexion η2p = 0.12–0.90; extension η2p = 0.29–0.42). No significant effect was present in the sham condition. Flexion ROM decreased whereas the extension ROM increased, depending on SKD location- and displacement direction (p < 0.05). The ICC indicates a good intertester and intratester reliability (resp. ICC3,k = 0.81–0.93; ICC3,1 = 0.70–0.84). Lumbodorsal SKD affects the flexion- and extension spine, pelvis, and hip range of motion. The effects of SKD are direction- and location dependent as well as movement (flexion/extension) specific. Lumbodorsal SKD during flexion and extension may be useful to determine whether or not a patient would benefit from fascia tissue manipulations. Further research is required to obtain insight into the mechanisms via which the SKD affects ROM and muscle activation, in healthy, asymptomatic-LBP, and LBP subjects.